03basisinformation - Reddeker, Lioba (Wien : Basis Wien - Kunst, Information und Archiv, 1998)
Deutschbauer, Julius ; Goldblatt, Karl ; Scheffknecht, Romana ; Wachsmuth, Arye & Simon ; Muntean, Markus ; Rosenblum, Adi ; Gelatin, Gruppe ; Krenn, Martin ; Brunner-Szabo, Eva ; Tschögl, Gert ; Lederer, Adolf ; Orsini-Rosenberg, Markus
Duits
boek